Two-stage treatment of skeletal Class II malocclusion: case report (Research, Society and Development, 2023)
Objective: class II malocclusion is one of the most frequent problems in orthodontics and is characterized by maxillary prognathism, mandibular retrognathism, or both. The aim of this study is to report the case of a patient with Angle Class I and Skeletal Class II malocclusion in the growth phase treated in two phases with AEB and orthodontic mini-implant. Case report: female patient, 9 years old, reported an accentuated projection of the anterior teeth. She had the habit of interposing the lower lip, dolichofacial pattern, Angle Class I molars, and great projection of the upper incisors. In the first phase was used AEB, and in the second phase an interradicular mini screw with sliding jig to finalize Class II correction on the left side. Conclusion: it’s evident the benefits of first orthopedic/functional phase in overbite correction and success of the proposed treatment through the stability after 4 years of case management.